Instability of Suicidal Ideation in Patients Hospitalized for Depression: An Exploratory Study Using Smartphone Ecological Momentary Assessment. Issue 1 (2nd January 2022) - Peters, Evyn M.; Dong, Lisa Yue; Thomas, Teena; Khalaj, Sara; Balbuena, Lloyd; Baetz, Marilyn; Osgood, Nathaniel; Bowen, Rudy
Abstract: This study used ecological momentary assessment (EMA) to explore the correlates of suicidal ideation (SI) instability in patients hospitalized for depression and SI. Thirty-nine adult inpatients were given smartphones with visual analogue scales to rate current depressed mood, anger/irritability, feeling socially connected, and SI three times a day throughout hospitalization. Affective Lability Scales (ALS) were also completed at baseline. SI instability was correlated with SI intensity, depressed mood instability, and social connection instability. Social connection instability was not associated with SI instability after controlling for depressed mood instability. ALS scores were not associated with EMA-derived SI instability. Participants with multiple past suicide attempts experienced greater SI instability. More research examining the clinical significance of SI instability is warranted.